2008
DOI: 10.2174/1874282300802010217
|View full text |Cite
|
Sign up to set email alerts
|

Target Atmospheric CO: Where Should Humanity Aim?

Abstract: Dyadic data matrices, such as co-occurrence matrix, rating matrix, and proximity matrix, arise frequently in various important applications. A fundamental problem in dyadic data analysis is to find the hidden block structure of the data matrix. In this paper, we present a new coclustering framework, block value decomposition(BVD), for dyadic data, which factorizes the dyadic data matrix into three components, the row-coefficient matrix R, the block value matrix B, and the column-coefficient matrix C. Under thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
752
1
11

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,021 publications
(807 citation statements)
references
References 138 publications
21
752
1
11
Order By: Relevance
“…The data further suggest that the planet was largely ice free until atmospheric CO 2 concentrations fell to 450 ppm (±100 ppm), indicating a danger zone when concentrations of CO 2 rise within the range of 350 -550 ppm (Hansen et al 2008). Despite uncertainties related to the degree of hysteresis in the relationship between ice growth and ice creation in response to temperature change, the above suggests that raising CO 2 concentration above 350 ppm may lead to crossing a threshold that results in the eventual disappearance of some of the large polar ice sheets, with a higher risk of crossing the threshold as the CO 2 concentration approaches the upper end of the range.…”
Section: Climate Changementioning
confidence: 87%
See 2 more Smart Citations
“…The data further suggest that the planet was largely ice free until atmospheric CO 2 concentrations fell to 450 ppm (±100 ppm), indicating a danger zone when concentrations of CO 2 rise within the range of 350 -550 ppm (Hansen et al 2008). Despite uncertainties related to the degree of hysteresis in the relationship between ice growth and ice creation in response to temperature change, the above suggests that raising CO 2 concentration above 350 ppm may lead to crossing a threshold that results in the eventual disappearance of some of the large polar ice sheets, with a higher risk of crossing the threshold as the CO 2 concentration approaches the upper end of the range.…”
Section: Climate Changementioning
confidence: 87%
“…The boundary is based on (i) an analysis of the equilibrium sensitivity of the climate system to greenhouse gas forcing; (ii) the behaviour of the large polar ice sheets under climates warmer than those of the Holocene (Hansen et al 2008); and (iii) the observed behaviour of the climate system at a current CO 2 concentration of about 387 ppm and +1.6 W m -2 (+0.8/-1.0 W m -2 ) net radiative forcing (IPCC 2007a)).…”
Section: Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…This time Parties are following a 'bottom-up' model (Dubash and Rajamani, 2010, p. 594), in which countries pledge what they are able or willing to contribute. Yet, the Intended Nationally Determined Contributions (INDCs) that have so far been announced fall far short of bringing the world on a below 2°C trajectory (Climate Action Tracker, 2015), let alone 1.5°C as some have called for (Hansen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies suggest that reductions of N 2 O emissions from biochar-treated soil depended on soil moisture and soil aeration. When biochar was applied to soil the GHG emissions were 12%-84% lower than when biochar was combusted directly for energy purposes (Hansen et al, 2008). Even though numbers of researches of biochar have been reported about the potential of sequestrating carbon and reducing GHG emission, few studies have been reported in a practical field scale especially conventional rice cropping system under the different water regime in the US.…”
Section: Introductionmentioning
confidence: 99%